MODEL KOMUNIKASI ANTARBUDAYA ETNIS MADURA DAN ETNIS DAYAK DI DESA BASAWANG KABUPATEN KOTAWARINGIN TIMUR PROVINSI KALIMANTAN TENGAH - Khadijah Khadijah (Transformatif, 2018)
This study tries to explore on How the intercultural communication of Madurese ethnic and Dayak ethnics in Basawang Village, East Kotawaringin Regency, Central Kalimantan Province after the ethnic war at 2001. Researchers assume that this research is interesting because after the ethnic war at 2001 in the Village of Basawang Ethnic Dayak with Ethnic Madurese living together, in a harmonious and conducive state, there had even been an inter-ethnic language exchange. This phenomenon is being uncovered by using qualitative research method, the research that has the nature of describing situations and events, the data is stated in a makeshift condition, by describing the workings that are systematic, directed and accountable, so as not to lose their scientific nature. The result indicates that as a theory of intercultural communication model according to William B. Ludykunst and Young Yun Kim, this can be seen from the perceptions of the two ethnicities. Based on the two perceptions of the two ethnicities, the form of intercultural communication is mutual respect and respect for each other's ethnic customs. The relationship between the two ethnic groups has so far taken place without obstacles, which means that each ethnic group has accepted each other.